Relevansi Konsep Akad Wakalah Dalam Program Tapera Analisis Tinjauan Fiqih Muamalah - Haq, Dhiyaul; Mus’if , Ach (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2024)
This study examines the relevance of the wakalah bil ujrah contract in the Tapera program, a government-led housing financing scheme in Indonesia, from an Islamic law perspective. The research aims to assess the legal compliance of the Tapera program with Islamic principles and provide recommendations for its improvement. The study employs a descriptive qualitative approach with inductive analysis, utilizing data from scholarly journals, news articles about Tapera, and Islamic law literature. The research explores the concept of wakalah, the pillars and conditions of wakalah bil ujrah, and analyzes the suitability of these elements in the Tapera program based on participant perspectives. The findings reveal a lack of understanding among Tapera participants regarding the wakalah bil ujrah contract. The research highlights the need for comprehensive socialization to ensure a proper understanding of the contract's pillars and conditions. The study emphasizes the importance of legal compliance with Islamic principles in the Tapera program and recommends intensive socialization to enhance participant understanding of the wakalah bil ujrah contract, ensuring its validity and effectiveness, and aligning the program with Islamic principles. [Penelitian ini mengkaji relevansi akad wakalah bil ujrah dalam program Tapera, sebuah skema pembiayaan perumahan yang dipimpin oleh pemerintah di Indonesia, dari perspektif hukum Islam. Penelitian ini bertujuan untuk menilai kepatuhan hukum program Tapera dengan prinsip-prinsip Islam dan memberikan rekomendasi untuk perbaikannya. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan analisis induktif, memanfaatkan data dari jurnal ilmiah, artikel berita tentang Tapera, dan literatur hukum Islam. Penelitian ini mengeksplorasi konsep wakalah, rukun dan syarat wakalah bil ujrah, dan menganalisis kesesuaian unsur-unsur tersebut dalam program Tapera berdasarkan perspektif peserta. Temuan penelitian menunjukkan kurangnya pemahaman di antara para peserta Tapera mengenai akad wakalah bil ujrah. Penelitian ini menyoroti perlunya sosialisasi yang komprehensif untuk memastikan pemahaman yang tepat mengenai rukun dan syarat akad. Penelitian ini menekankan pentingnya kepatuhan hukum terhadap prinsip-prinsip syariah dalam program Tapera dan merekomendasikan sosialisasi intensif untuk meningkatkan pemahaman peserta mengenai akad wakalah bil ujrah, memastikan keabsahan dan keefektifannya, serta menyelaraskan program dengan prinsip-prinsip syariah].